2017
DOI: 10.1039/c6ra28426d
|View full text |Cite
|
Sign up to set email alerts
|

The novel iminium surfactant p-benzylidene benzyldodecyl iminium chloride as a corrosion inhibitor for plain carbon steel in 1 M HCl: electrochemical and DFT evaluation

Abstract: The iminium surfactant p-benzylidene benzyldodecyl iminium chloride was synthesized, characterized and evaluated as a novel corrosion inhibitor for plain carbon steel in 1 M HCl solution at 30, 40, 50 and 60 C using gravimetric analysis, spectrophotometric analysis of iron ions, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and density functional theory (DFT). The evaluated compound acted as an efficient corrosion inhibitor for plain carbon steel in 1 M HCl solution. The inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Sometimes, iminium compounds reduce surface heterogeneity, caused by adsorption of ionic liquid over the metal surface. Apparently, elemental analysis of the inhibited metal showed that the inhibitor's constituents were 15 wt% of carbon and 10 wt% of oxygen, and also corroborated that dodecyl iminium chloride is more favorably adsorbed than the non-alkylated form [30].…”
Section: Significance Of Carbon Chain Length On Surface Protection Ofmentioning
confidence: 80%
“…Sometimes, iminium compounds reduce surface heterogeneity, caused by adsorption of ionic liquid over the metal surface. Apparently, elemental analysis of the inhibited metal showed that the inhibitor's constituents were 15 wt% of carbon and 10 wt% of oxygen, and also corroborated that dodecyl iminium chloride is more favorably adsorbed than the non-alkylated form [30].…”
Section: Significance Of Carbon Chain Length On Surface Protection Ofmentioning
confidence: 80%
“…Moreover, the CPE decreased with an increase in the thickness of the organic-inorganic coating, which could be attributed to the improvement in the surface of the electrical double layer 37 . The organic-inorganic materials between the charged AZ31 Mg surface and the NaCl solution could be considered as an electrical capacitor 41,42 . This is very important because higher resistance (Rct) indicate better inhibition performance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was evident that both DEIP and TiO 2 exhibited a synergistic effect that led to higher resistance of all parts of the coating layers. On the other hand, the CPE decreased with an increase in the coating thickness, which can be attributed to enhancement of the thickness of the electrical double layer 66 . The coating layers between the charged metal surface and the solution can be considered as an electrical capacitor 65 , 66 .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the CPE decreased with an increase in the coating thickness, which can be attributed to enhancement of the thickness of the electrical double layer 66 . The coating layers between the charged metal surface and the solution can be considered as an electrical capacitor 65 , 66 . In addition, the charge transfer resistance (Table 4 ) increased with an increase in the concentration of the inhibitor.…”
Section: Discussionmentioning
confidence: 97%